Reseña/Review (Jiang, Y., "Cyber-nationalism in China: challenging Western media portrayals of internet censorship in China". University of Adelaide, ISBN: 9780987171894, 156 págs., 2012) - Ferguson, Jonathan (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2015)
Reseña/Review (Jiang, Y., "Cyber-nationalism in China: challenging Western media portrayals of internet censorship in China". University of Adelaide, ISBN: 9780987171894, 156 págs., 2012)